2021
DOI: 10.1038/s41598-021-84723-7
|View full text |Cite
|
Sign up to set email alerts
|

Key factors in a rigorous longitudinal image-based assessment of retinopathy of prematurity

Abstract: To describe a database of longitudinally graded telemedicine retinal images to be used as a comparator for future studies assessing grader recall bias and ability to detect typical progression (e.g. International Classification of Retinopathy of Prematurity (ICROP) stages) as well as incremental changes in retinopathy of prematurity (ROP). Cohort comprised of retinal images from 84 eyes of 42 patients who were sequentially screened for ROP over 6 consecutive weeks in a telemedicine program and then followed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Serial evaluation of fundus photos has demonstrated value in detecting signs of disease progression ( 22 ). We found that en face visualization provided sufficient detail to assess relative changes in disease severity across time ( Figure 3A ) by direct comparison to prior images.…”
Section: Resultsmentioning
confidence: 99%
“…Serial evaluation of fundus photos has demonstrated value in detecting signs of disease progression ( 22 ). We found that en face visualization provided sufficient detail to assess relative changes in disease severity across time ( Figure 3A ) by direct comparison to prior images.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have supported its validity and diagnostic accuracy in the context of telemedicine with a remote physician or even trained technicians reading the images 6 12 . The documentation provided by fundus photos additionally enables direct comparison among sessions, allowing for tracking of both disease progression 13 and treatment response 14 , 15 .…”
Section: Discussionmentioning
confidence: 99%